A Comparison of Different Modulation Techniques for Muli-Coil Inductive Power Transfer - Domajnko, Jure; Milanovič, Miro; Prosen, Nataša (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The Inductive Power Transfer (IPT) is the most popular method of transferring power wirelessly. In order to increase the transferred power, the multi-coil structure can be used. This can also impacts the tolerance to misalignment and rotation between coils. In order to control output voltage, multiple different transmitter modulation techniques can be used. To choose the most suitable modulation method, the most popular modulation methods were implemented on the multi-coil system and experimentally tested under the same working conditions.